Barcoding Fails to Delimit Species in Mongolian Oedipodinae (Orthoptera, Acrididae) - Lea-Sophie Kock; Elisabeth Körs; Martin Husemann; Lkhagvasuren Davaa; Lara-Sophie Dey (Insects, 2024)
Mongolia, a country in central Asia, with its vast grassland areas represents a hotspot for Orthoptera diversity, especially for the Acrididae. For Mongolia, 128 Acrididae species have been documented so far, of which 41 belong to the subfamily Oedipodinae (band-winged grasshoppers). Yet, few studies concerning the distribution and diversity of Oedipodinae have been conducted in this country. Molecular genetic data is almost completely absent, despite its value for species identification and discovery. Even, the simplest and most used data, DNA barcodes, so far have not been generated for the local fauna. Therefore, we generated the first DNA barcode data for Mongolian band-winged grasshoppers and investigated the resolution of this marker for species delimitation. We were able to assemble 105 DNA barcode (COI) sequences of 35 Oedipodinae species from Mongolia and adjacent countries. Based on this data, we reconstructed maximum likelihood and Bayesian inference phylogenies. We, furthermore, conducted automatic barcode gap discovery and used the Poisson tree process (PTP) for species delimitation. Some resolution was achieved at the tribe and genus level, but all delimitation methods failed to differentiate species by using the COI region. This lack of resolution may have multiple possible reasons, which likely differ between taxa: the lack of resolution in the Bryodemini may be partially explained by their massive genomes, implying the potential presence of large numbers of pseudogenes, while within the Sphingonotini incomplete lineage sorting and incorrect taxonomy are more likely explanations for the lack of signal. Further studies based on a larger number of gene fragments, including nuclear DNA, are needed to distinguish the species also at the molecular level.